Perspectives on Grandparenthoods in sociocultural contexts (Research, Society and Development, 2024)
This article presents reflections on grandparenthood resulting from a seminar entitled International Seminar on Grandparenthood in Sociocultural Contexts, by the Catholic University of Salvador – Bahia, Brazil held in celebration of International Grandparents Day, on July 26, 2024, online. It aimed to report the advances and challenges found in intergenerational relationships between grandparents and grandchildren approached by researchers from Brazil, Uruguay and Portugal and, in this way, promoting in-depth academic and professional debate. A documental, reflexive and qualitative research was done based on Seminar oral presentations. The corpus of this article is divided into six thematic axes, corresponding to the presentations of the various invited researchers: (1) the experience of being a grandmother; (2) grandparents in cyberspaces; (3) the challenges that permeate the relationship between grandparents and grandchildren; (4) grandparents with dementia; (5) marriage and grandparenthood; (6) grandparents caregivers and grandchildren’s schooling. It is concluded, from the presentations, that the theme of grandparents has a broad scope, covering the personality of grandparents, the social area in which grandparents are caregivers and providers and care related to health and education. In this way, the Seminar fostered the desire to disseminate knowledge shared by academics from national and international universities, highlighting possibilities and challenges in different sociocultural contexts.